Role of Postinjection Antibiotics after Intravitreal Bevacizumab Injection in Preventing Endophthalmitis - Ali Muhammad Abbasi, Muhammad Afzal Pachuo, Amjad Ali Sahto, Muhammad Hashim Quraishi (Pakistan Journal of Ophthalmology, 2015)
Purpose: To evaluate the role of using antibiotics after intravitreal injection of Bevacizumab in patients to prevent postinjection endophthalmitis. Material and Methods: A multicentre prospective case control study was carried out at PUMHSW Hospital Nawabshah and Ghulam Muhammad Mehar Medical college Hospital Sukkhur. The injection was given by different surgeons but with same technique. Immediately after intravitreal Bevacizumab injection the patient was started with Topical Moxifloxacin and oral ciprofloxacin 500 mg for three days. Patients were followed at 1st, 2nd and 4th week post-injection to look for any sign of endophthalmitis. Result: Out of 620 injections given in 480 eyes, 310 were control group without any post-injection medicine and 310 were cases who were given post-injection medicine. No case of proven or suspected endophthalmitis was identified, corresponding to a risk of 0% per injection. Conclusion: In our study use of antibiotics after intravitreal Bevacizumab injection does not make any difference for the prevention of postoperative endophthalmitis. Keywords: Endophthalmitis, Bevacizumab,Intravitreal Antibiotics.